1999
DOI: 10.1034/j.1600-0420.1999.770507.x
|View full text |Cite
|
Sign up to set email alerts
|

Pulsatile ocular blood flow in diabetic retinopathy

Abstract: ABSTRACT.Purpose: To assess circulatory properties of eyes with progressive stages of diabetic retinopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
33
0
6

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(42 citation statements)
references
References 20 publications
3
33
0
6
Order By: Relevance
“…13 It has been clinically found to be reduced in a variety of ocular diseases including glaucoma, 14 age-related macular degeneration, 15,16 and diabetic retinopathy. 17 Our previous study has shown that GO patients had significantly reduced POBF as compared to those with Graves' disease only or healthy subjects. 8 GO is an autoimmune disorder, in which orbital connective tissues often undergo a dramatic remodelling, including intense inflammation and accumulation of the hydrophilic glycosaminoglycan.…”
Section: Discussionmentioning
confidence: 90%
“…13 It has been clinically found to be reduced in a variety of ocular diseases including glaucoma, 14 age-related macular degeneration, 15,16 and diabetic retinopathy. 17 Our previous study has shown that GO patients had significantly reduced POBF as compared to those with Graves' disease only or healthy subjects. 8 GO is an autoimmune disorder, in which orbital connective tissues often undergo a dramatic remodelling, including intense inflammation and accumulation of the hydrophilic glycosaminoglycan.…”
Section: Discussionmentioning
confidence: 90%
“…The pulsatile component of ocular blood flow is primarily choroidal. 5 It has been clinically applied to investigate in various ocular diseases including glaucoma, 6,7 age-related macular degeneration, 8,9 diabetic retinopathy, 10,11 choroidal melanoma, 12 and retinal pigmentosa. 13 Graves' disease (GD) is an autoimmune disorder characterized by hyperthyroidism, diffuse goitre, ophthalmopathy, and rarely, dermopathy.…”
Section: Introductionmentioning
confidence: 99%
“…POBF assessment may be of clinical importance in the detection and monitoring of several eye diseases. It has been found to be reduced A study comparing ocular pressure pulse and ocular fundus pulse in dependence of axial eye length and ocular volume in glaucoma (Perkins 1981a;Quaranta et al 1994;Stalmans et al 2008) and characteristically altered in other vascular-related ocular pathology, such as diabetic retinopathy (MacKinnon et al 1997;Geyer et al 1999) and exudative age-related maculopathy (Mori et al 2001a). In recent years there has been increased interest in the interpretation of the ocular pulse amplitude, because it is measured easily using dynamic contour tonometry (Punjabi et al 2006a(Punjabi et al , 2006b).…”
Section: Introductionmentioning
confidence: 99%